A novel CLCN5 frame shift mutation responsible for Dent disease 1: Case report - Ni, Jiajia; Zhu, Yaju; Lin, Fujun; Guan, Wenbin; Jin, Jing; Li, Yufeng; Guo, Guimei (Frontiers in Pediatrics, 2022)
Background Dent disease is a group of inherited X-linked recessive renal tubular disorders. This group of disorders is characterized by low molecular weight proteinuria (LMWP), nephrocalcinosis, hypercalciuria and renal failure. Case presentation Here we report one 11-year-old Chinese boy (proband) and one 13-year-old Chinese boy who was proband’s cousin, both presented with massive proteinuria. Further laboratory examinations revealed a lack of nephrocalcinosis, nor any other signs of tubular dysfunction, but only LMWP and hypercalciuria. There was no abnormality in growth, renal function or mineral density of the bones. A de novo deletion (c.1448delG) in the CLCN5 gene was identified, resulting in a frameshift mutation (p.Gly483fs). The proband’s and his cousin’s mothers were found to be the carrier of this mutation. Conclusions In this study, we have found a novel frameshift mutation (c. 1448delG) at exon 11 of the CLCN5 gene which leads to Dent disease 1, expanding the spectrum of CLCN5 mutations.